Pengaruh Reputasi Perusahaan, Kompensasi Dan Lingkungan Kerja Terhadap Minat Melamar Pekerjaan - Catur Sasi Kirono; Sri Wahyuningsih; Supartono Supartono (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study aims to determine the effect of company reputation, compensation and work environment on interest in applying for a job for at Pt Katolec Indonesia. Respondents to this study were 94 people (population 123 people) Pelita Bangsa students majoring in management class of 2019. This type of research is quantitative and data processing techniques use SPSS version 26.The results of this study indicate that the company's reputation variable has a significant positive effect on the intention to apply variable with a regression coefficient value of 0.319 or 31.9%, the compensation variable has a significant positive effect on the interest in applying variable with a regression coefficient value of 0.256 or 25.6 % while the work environment variable has a significant negative effect on the interest in applying variable with a regression coefficient of -0.109 or -10.9%.